If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -31 = -20 Reorder the terms: -31 + 11x = -20 Solving -31 + 11x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '31' to each side of the equation. -31 + 31 + 11x = -20 + 31 Combine like terms: -31 + 31 = 0 0 + 11x = -20 + 31 11x = -20 + 31 Combine like terms: -20 + 31 = 11 11x = 11 Divide each side by '11'. x = 1 Simplifying x = 1
| x+9.8=14.5 | | 7=y-12 | | 3x-17=16-(2x+8) | | 2x+12=90+3x+23 | | 30x+3=123 | | 16x+420=-100 | | 7-2=13-3 | | 4(y+3)+7=4y+19 | | 22=5x+7 | | X^3-2x^2+5x-1=0 | | 6+2f=20-3f | | 3(y+6)=2(y+4) | | 18[m+0.44]-16=118 | | 4(3x-8)=16 | | -102+7x=7x+24 | | 2x+x^2-35=0 | | x-3.7=3.5 | | -14(3a+6)=12(6-4a)+12 | | 3(y-7)=21 | | 8x-2=94 | | 2(s+1)=12 | | 8p+3=23 | | 9+7r=13 | | 5+5y=25 | | 4(x-3)=-16-1 | | 15=y-13 | | f-5=8 | | 7x-3=109 | | 25-y=13 | | 9-0.25j=5 | | 2x+5x+3y-y=35 | | 2x+12=3x+23 |